Effect of replacing dried skim milk with specially processed soy products on digestibility of nutrients and growth performance of nursery pigs - D B Jones; P G Reddy; R D Klemm; Frank Blecha; Joe D Hancock (Kansas Agricultural Experiment Station Research Reports, 1990)
One hundred twenty-eight pigs (21 d of age and 11.7 lb) were used to determine the effects of feeding specially processed soy products and lactose versus dried skim milk on growth performance and nutrient digestibility. For d 0-14, pigs received pelleted diets that were: 1) corn-soybean meal-whey control; 2) a high nutrient density diet (HNDD) containing 20% dried skim milk and 20% dried whey; 3 and 4) the HNDD with soy protein isolate replacing 50% and 100% of the protein supplied by dried skim milk; 5 and 6) the HNDD with soy protein concentrate replacing 50% and 100% of the protein supplied by dried skim milk; 7 and 8) the HNDD with modified soy flour replacing 50% and 100% of the protein supplied by dried skim milk. For d 14-35, all pigs were fed a common diet. Average daily gain (ADG), average daily feed intake (ADFI), feed:gain ratio (F/G), and fecal scores were determined for d 7, 14, and 35 of the experiment. Apparent digestibilities of N and DM were determined from fecal samples collected on d 13. For d 0 to 7, pigs fed the HNDD had the best F/G, pigs fed the corn-soybean meal-whey control had the poorest F/G, and pigs fed diets with the specially processed soy products were intermediate in feed efficiency. Pigs fed the soy isolate had improved feed efficiency and less incidence of diarrhea compared to pigs fed the soy concentrate. For d 0 to 14, pigs fed the corn-soybean meal-whey control had the poorest performance and DM digestibility. When dried skim milk was replaced with the specially processed soy products, F/G was worse, but digestibility of N and DM were not decreased, especially at the 50% level of replacement. Pigs fed the soy isolate had performance more similar to pigs fed the HNDD than pigs fed the soy concentrate or modified soy flour. From d 0 to 35, ADG and ADFI were greater for pigs fed diets with soy products replacing the protein from dried skim milk than pigs given the HNDD. However, pigs fed the HNDD gained more efficiently. Our data indicate that replacing the protein from dried skim milk with the specially processed soy products tested in this experiment resulted in slight depressions in performance early in the nursery phase (ie., d 0 to 14). However, as the processing techniques became more elaborate (ie., isolate>concentrate>modified soy flour), utilization of the products was improved.; Swine Day, Manhattan, KS, November 15, 1990
Keywords: Swine day; 1990; Kansas Agricultural Experiment Station contribution; no. 91-189-S; Report of progress (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service); 610; Swine; Starter; Performance; Soybean; SBM; DSM